Pelatihan Konversi Biomass Sawit Menjadi Geo-Textile Nonwoven untuk Kemandirian Ekonomi Desa Wirajaya Kabupaten Bogor - Nikmatin, Siti; Setyaningsih, Luluk; Denih, Asep; Irmansyah, Irmansyah; Zuhri, Mahfuddin; Adiati, Rima Fitria (Jurnal Pengabdian UNDIKMA, 2025)
The purpose of the PDTI program’s community service activities is to achieve economic independence through the processing of OPEFB into geotextiles and creative industries. The implementation method uses training and assistance in processing OPEFB into fiber using fibrillation milling tools and arranging them into non-woven textile sheets to be applied in diversifying products with high economic value. Participants in PDTI activities are farmer groups from Wirajaya Village, Bogor Regency, which is <100 m from the IPB Dramaga. The evaluation instrument uses pretest and posttest on the quantitative value of knowledge, skills, and motivation in absorbing the technology provided through training. The results of the evaluation showed a significant improvement in people’s knowledge, skills, and motivation. This program not only opens up new business opportunities but also contributes to environmental conservation through organic waste reduction and the promotion of a circular economy. In addition, this program has also increased to have a positive impact on the community in terms of knowledge, motivation, and skills. Meanwhile, the results of intensive training and assistance to the community are also able to convert waste into value-added products such as nonwoven geotextiles.